Aplicação do projeto sandbox de realidade aumentada como uma atração interativa tecnológica para museus utilizando conceitos de user experience - Bainy, Matheus Gonçalves (2018)
Based on the modernization process of museums, this work aims to evaluate the Sandbox as an interactive technological attraction in museums and science institutes in order to adapt to these new museum concepts. A study was carried out regarding the types of education, the functioning of technological museums and the rules regarding interactive technological attractions. Resulting in the definition of three pillars for analysis: complexity, effectiveness and fun. These items were evaluated through an observational field survey conducted at the Science Station and the Itaipu Tourist Complex, both in Foz do Iguaçu, where participants interacted with the Sandbox. At the end, the conclusions were positive and the Sandbox was effective in meeting the three evaluated items.